Immunohistochemical expression of interlukin10 (IL10) and heat shock protein-90 (HSP-90) in prostatic carcinoma - Wasan Abdul-ilah Bakir; Hiba Ahmed Gaidan; Methaq Mueen Al-kaabi (Wolters Kluwer Medknow Publications, 2020)
Background: Specific cytokines are related to pathologically changed prostate, propose that the balance in cytokine differs in normal and pathological prostate. Of these cytokines the interleukins 10, due to its "pleiotropic" actions in inflammation and angiogenesis, and HSP-90 due to its expression in tumor cells at high levels, suggesting that it has an important role for growth and/or survival of tumor cells. Aims: Evaluation of HSP-90 and IL10 immunoreactivity in benign prostatic hyperplasia (BPH) and prostatic carcinoma and to correlate this expression with clinicopathological parameters. Settings and Design: A retrospective study in which 83 Paraffin-embedded tissue specimens including (43) BPH, (40) prostatic carcinoma and (20) normal prostate as control were included between the period of January 2015 and January 2017. Patients, Material and Methods: All the cases were evaluated histopathologically and stained immunohistochemically for IL10 and HSP-90. Only cytoplasmic staining was considered as positive. Immunoreactivity scoring for both markers expression was calculated based on both staining intensity and percentage. Statistical Analysis: Was done using SPSS Version 21 statistical analysis software. P value of <0.05 was considered statistically significant. Result: Statistical analysis of HSP-90 and IL10 expression revealed a highly significant correlation of expression of these two markers in advanced Gleason grading and tumor, node, and metastasis (TNM) staging cases of prostatic carcinoma. Conclusion: High expression of IL10 and HSP-90 is associated with high grade and stage of prostatic carcinoma. This provides a base for further studies and researches on the role of these investigated proteins as prognostic markers immunotherapy targets for carcinoma of the prostate.